FAMILY WELFARE FISHERIES OF AKIT TRUST BANTAN TIMUR VILLAGE OF BENGKALIS REGENCY RIAU PROVINCE - Rafi kurniawan; Firman Nugroho; Zulkarnain Umar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Characteristics of fishermen of the Akit tribe included in the very productive age, the level of education is low, the average income of fishermen of the Akit Tribe is still below the Bengkalis Regency Regional Minimum Wage (Rp. 2,919,000 per month with an average expenditure of Rp. 1,800,000 per month and the number of dependents of the Akit tribe fishermen in Bantan Timur Village is 5 people on average. Social characteristics of fishermen The Akit tribe: inherit the fishing profession, believe in mystical or superstitious things, have difficulty interacting with other community groups.From the research conducted, it was found that the fishing families of the Akites in the East Bantan Village belonged to underprivileged families with a percentage of 45.8%, stage I prosperous families with a percentage of 33.4% and stage II prosperous families with a percentage of 20.8%. so it can be concluded that most of the Akit fishing families in Bantan Timur Village are mostly poor families.The role of the Bengkalis government in improving the welfare of the family of the Akit tribe is to make policies in the form of assistance given, such as Livable Houses, Fishing Assistance, Direct Cash Assistance (BLT), Rice for the poor (RASKIN), PNPM Mandiri assistance with such assistance alleviate and help the lives of the people of the Akit tribe. Keyword: Welfare, Family Of Fishermen, Akit Trust